PENGARUH KEPEMILIKAN ASING, UKURAN PERUSAHAAN, LEVERAGE,DAN BEBAN PAJAK TERHADAP TRANSFER PRICING - Nadiah Adilah; Dirvi Surya Abbas; Imam Hidayat; Budi Rohmansyah (Akuntansi, 2022)
The purpose of this study was to determine the effect of foreign ownership, firm size, leverage and profitability on transfer pricing, empirical studies of mining companies listed on the Indonesia Stock Exchange (IDX). The period used in this study is 5 (five) years, starting from 2017 - 2021.This study uses a quantitative approach. The population in this study is 44 mining companies listed on the Indonesia Stock Exchange. The sampling technique used is Purpoisve Sampling. Based on the predetermined criteria obtained 9 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX) website. The analytical method used is panel data regression analysis.The results showed that simultaneously. Foreign Ownership, Company Size, Leverage and Tax Burden together have an effect on Transfer Pricing. Partially Company Size has a negative effect on Transfer Pricing, while Foreign Ownership, Leverage has no effect on Transfer Pricing. But the tax burden has an effect on transfer pricing.